Sensitivity of GBM cells to cAMP agonist-mediated apoptosis correlates with CD44 expression and agonist resistance with MAPK signaling - Daniel, Paul M (Cell Death Dis, 2016)
In some cell types, activation of the second messenger cAMP leads to increased expression of proapoptotic Bim and subsequent cell death. We demonstrate that suppression of the cAMP pathway is a common event across many cancers and that pharmacological activation of cAMP in glioblastoma (GBM) cells leads to enhanced BIM expression and apoptosis in specific GBM cell types. We identified the MAPK signaling axis as the determinant of cAMP agonist sensitivity in GBM cells, with high MAPK activity corresponding to cAMP resistance and low activity corresponding to sensitization to cAMP-induced apoptosis. Sensitive cells were efficiently killed by cAMP agonists alone, while targeting both the cAMP and MAPK pathways in resistant GBM cells resulted in efficient apoptosis. We also show that CD44 is differentially expressed in cAMP agonist-sensitive and -resistant cells. We thus propose that CD44 may be a useful biomarker for distinguishing tumors that may be sensitive to cAMP agonists alone or cAMP agonists in combination with other pathway inhibitors. This suggests that using existing chemotherapeutic compounds in combination with existing FDA-approved cAMP agonists may fast track trials toward improved therapies for difficult-to-treat cancers, such as GBM.